Determinantes e consequências do excesso ventilatório no exercício progressivo na associação doença pulmonar obstrutiva crônica e insuficiência cardíaca - Figueredo Junior, Alcides Rocha De [UNIFESP] (2018)
Rationale: An increased ventilatory response to exertional metabolic demand (high ventilation (⩒E)-‐carbon dioxide output (⩒CO2) relationship) is a common finding in patients with coexistent chronic obstructive pulmonary disease (COPD) and heart failure (HF). Objectives: We aimed to determine the mechanisms underlying high ⩒E-‐⩒CO2 and its impact on operating lung volumes, dyspnea, and exercise tolerance in these patients. Methods: Twenty-‐two ex-‐smokers with combined COPD and HF with reduced left ventricular ejection fraction (LVEF) undertook, after careful treatment optimization, a progressive cycle exercise test with capillary (c) blood gas collection. Measurements and Main Results: Regardless of the chosen metric (increased ⩒E-‐⩒CO2 slope, ⩒E /⩒CO2 nadir or end-‐exercise ⩒E /⩒CO2), ventilatory inefficiency was closely related to PcCO2 (r values from −0.80 to −0.84; p < 0.001) but not dead space/tidal volume ratio. Ten patients consistently maintained exercise PcCO2 less than or equal to 35 mm Hg (hypocapnia). These patients had particularly poor ventilatory efficiency compared with patients without hypocapnia (p < 0.05). Despite the lack of between-‐ group differences in spirometry, lung volumes, and left ventricular ejection fraction, patients with hypocapnia had lower resting PaCO2 and lung diffusing capacity (p < 0.01). Excessive ventilatory response in this group was associated with higher exertional PcO2. The group with hypocapnia, however, had worse mechanical inspiratory constraints and higher dyspnea scores for a given work rate leading to poorer exercise tolerance compared with their counterparts (p < 0.05). Conclusions: Increase in neural drive promoting a ventilatory response beyond that required to overcome an increased “wasted” ventilation led to hypocapnia and poor exercise ventilatory efficiency in COPD-‐HF overlap. Excessive ventilation led to better arterial oxygenation but at the expense of earlier critical mechanical constraints and intolerable dyspnea.